Bile acids and coronavirus disease 2019 - Xiaoru Huang; Xuening Liu; Zijian Li (Elsevier, 2024)
The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been significantly alleviated. However, long-term health effects and prevention strategy remain unresolved. Thus, it is essential to explore the pathophysiological mechanisms and intervention for SARS-CoV-2 infection. Emerging research indicates a link between COVID-19 and bile acids, traditionally known for facilitating dietary fat absorption. The bile acid ursodeoxycholic acid potentially protects against SARS-CoV-2 infection by inhibiting the farnesoid X receptor, a bile acid nuclear receptor. The activation of G-protein-coupled bile acid receptor, another membrane receptor for bile acids, has also been found to regulate the expression of angiotensin-converting enzyme 2, the receptor through which the virus enters human cells. Here, we review the latest basic and clinical evidence linking bile acids to SARS-CoV-2, and reveal their complicated pathophysiological mechanisms.